Immunobiology : (Garland Pub, 2001)
The central thesis of this book is that the immune system exists to protect the host from infection and that its evolutionary history was shaped by this challenge. Other aspects of immunology are variations on the basic protective function. The first part of the book summarizes the basic immunological concepts and introduces the main 'players'. The middle three parts deal with the main aspects of adaptive immunity. The last part integrates the material at the level of the complete organism in both health and disease.